An analysis of some study helps in the Wonder world of reading book I and proposed enrichment exercises - Mendoza, Rosamilla Arce 1925- (1967)
The purpose of the study is to determine the adequacy of the study helps in The Wonder World of Reading Book I in developing the four dimensional skills in reading. Results of the study aims to help the reading teachers in determining what reading skills need to be further developed in each of the selections taken up in the reading class and inspire them to explore the possibilities of each selection in developing more complex reading skills.